Freedom and Animal Welfare - Heather Browning (Animals, 2021)
The keeping of captive animals in zoos and aquariums has long been controversial. Many take freedom to be a crucial part of animal welfare and, on these grounds, criticise all forms of animal captivity as harmful to animal welfare, regardless of their provisions. Here, we analyse what it might mean for freedom to matter to welfare, distinguishing between the role of freedom as an intrinsic good, valued for its own sake and an instrumental good, its value arising from the increased ability to provide other important resources. Too often, this debate is conducted through trading intuitions about what matters for animals. We argue for the need for the collection of comparative welfare data about wild and captive animals in order to settle the issue. Discovering more about the links between freedom and animal welfare will then allow for more empirically informed ethical decisions regarding captive animals.